The influence of the rotor shape on the efficiency of the hydrodynamic heater - Nussupbekov, B.; Oshanov, Y.; Ovcharov, M.; Duisenbayeva, M.; Sharzadin, A.; Kongyrbayeva, A.; Amanzholova, M. (Eastern- European Journal of Enterprise Technologies, 2024)
The paper discusses issues related to the design of a hydrodynamic throttle type heater. The maximum angular velocities for cylindrical and conical shapes are determined from the condition of non-spilling of liquid from a rotating vessel. Theoretical studies have shown that the conical shape of the skirt is more optimal, since with an increase in the liquid level in the vessel within 0.02–0.09 m, the angular velocity decreases from 37.566 rad/s to 17.709 rad/s, respectively. In addition, with a taper of the vessel walls of 5° and a liquid level height of 0.02 m, the volume of the liquid is 11.0·10–5 m3. If to increase the liquid level to 0.09 m, then the volume of liquid will increase to 55.0·10–5 m3. At a taper of 10°, respectively, there is also an increase in the volume of liquid from 6.0·10–5 m3 to 42.0·10–5 m3. To establish a small increase in the temperature of the liquid when it is forced through the throttle holes, a transparent mockup was made. Experimental studies have shown the locking of air during the formation of a ring of liquid in the rotor cavity. In addition, it was found that the smaller the inner radius of the liquid ring, the higher the temperature of the pressed liquid through the throttle openings. For this purpose, a system for removing air from its rotor was provided in the hydrodynamic heater. When the rotor is running, the lateral outer walls of the conical skirt interact with the liquid, forcing it to rotate. The rotating liquid, rising along the walls of the housing, begins to interact with the lower part of the rotor, which negatively affects the operation of the hydrodynamic heater as a whole. For this purpose, a special flow directing cylinder was provided in the housing. When the liquid is forced through the throttle opening, there is a decrease in pressure and an increase in the velocity of the liquid. This leads to an increase in its kinetic energy, which is then converted into thermal energy due to friction between the liquid molecules. This principle is used in various systems such as heating systems, industrial processes or laboratory research. However, creating pressure in front of the throttle openings using the inertial forces of a rotating mass of liquid is a promising direction
Keywords: rotor drum; liquid temperature; cylinder rotation; liquid level; thermal energy